2021
DOI: 10.1007/s11606-021-06883-6
|View full text |Cite
|
Sign up to set email alerts
|

Thriving among Primary Care Physicians: a Qualitative Study

Abstract: BACKGROUND: Burnout is high in primary care physicians and negatively impacts the quality of patient care. While many studies have evaluated burnout, there have been few which investigate those physicians who are satisfied with their careers and life-a phenomenon we term "thriving." OBJECTIVE: To identify factors contributing to both career and life satisfaction through qualitative interviews. PARTICIPANTS: The subjects were primary care physicians. APPROACH: Qualitative interviews were performed between July … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
(31 reference statements)
2
15
0
Order By: Relevance
“…A theoretical model of thriving at work developed by Spreitzer et al 58 suggests that when employees feel energised and full of learning in the workplace, they are energised and willing to invest more time, energy, and effort in their work, resulting in a high level of thriving at work. This will further stimulate their identification with their organisations (ie, affective commitment), which will lead to a higher level of centripetal force towards their careers and the groups they work with (ie, continuance commitment), and a greater willingness to engage in organisational activities and construction out of their own strong sense of responsibility and mission (ie, normative commitment) 59. Additionally, employees' commitment to the organisation inevitably affects employees' attitudes or feelings toward work, which in turn affects their job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…A theoretical model of thriving at work developed by Spreitzer et al 58 suggests that when employees feel energised and full of learning in the workplace, they are energised and willing to invest more time, energy, and effort in their work, resulting in a high level of thriving at work. This will further stimulate their identification with their organisations (ie, affective commitment), which will lead to a higher level of centripetal force towards their careers and the groups they work with (ie, continuance commitment), and a greater willingness to engage in organisational activities and construction out of their own strong sense of responsibility and mission (ie, normative commitment) 59. Additionally, employees' commitment to the organisation inevitably affects employees' attitudes or feelings toward work, which in turn affects their job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…A semi-structured interview guide was developed by a prior study on physician satisfaction (Appendix A) [14] . The questions were derived from a review of the literature on physician well-being and focused on aspects of each participants' life and career which have contributed to a sense of thriving, including work environment, learning climate, social networks, institutional supports, and intrinsic personal characteristics.…”
Section: Interview Guidementioning
confidence: 99%
“…A semi-structured interview guide that was developed in a prior study of physician thriving among primary care attendings was used (Appendix). 29 The questions were derived from a review of the literature on physician well-being and focused on aspects of each participants' life and career which have contributed to a sense of thriving, including work environment, social networks, institutional supports, and intrinsic personal characteristics. 27,43…”
Section: Interview Guidementioning
confidence: 99%
“…A qualitative study among primary care attending physicians identified five domains associated with thriving: social connections, love of work, value-oriented practice, agency, and relationships with patients. 29 However, a similar qualitative study among resident physicians has not been conducted. Consequently, it is our aim to develop a conceptual model to better understand resident physician thriving and in so doing address this key gap in the research literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation